Advancing Automated and Connected Vehicles: Policy and Planning Strategies for State and Local Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 845: Advancing Automated and Connected Vehicles: Policy and Planning Strategies for State and Local Transportation Agencies assesses policy and planning strategies at the state, regional, and local levels that could influence private-sector automated vehicle (AV) and connected vehicle (CV) choices to positively affect societal goals. The report aims to assist agencies with exploring actions that might increase the likelihood that AV and CV technologies will have beneficial impacts on traffic crashes, congestion, pollution, land development, and mobility (particularly for older adults, youths under the age of 16, and individuals with disabilities).Strategies to Advance Automated and Connected Vehicles: Briefing Document accompanies the report and summarizes the key findings of the report. It is intended for state, regional, and local agency and political decision makers who are framing public policy making for these transformational technologies. The briefing document makes the case for taking action in spite of uncertainties and presents 18 policy and planning strategies that may be useful in advancing societal goals.
Keywords: Transportation and Infrastructure

TCRP Annual Report of Progress 2017 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB’s Transit Cooperative Research Program (TCRP) has released its annual report, which provides background and an overview of the program, status of each of TCRP’s projects, and a summary of some of the program's accomplishments for the year.
Keywords: Transportation and Infrastructure

Estimating Truck Trip Generation for Airport Air Cargo Activity - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 80: Estimating Truck Trip Generation for Airport Air Cargo Activity compiles existing information about air cargo truck trip generation studies. The existing literature and research regarding air cargo facility-related truck trip generation rates is limited in its scope and detail. In addition, the complexity of the modern air cargo industry makes it difficult to obtain the data necessary to develop truck trip generation rates. Access to such information could conceivably help a community plan and invest appropriately by accounting for air cargo’s impacts. Similarly, air cargo operators and airport officials could employ such data to help ensure cargo facility truck access and egress remains reliable and safe.
Keywords: Transportation and Infrastructure

Statewide and Megaregional Travel Forecasting Models: Freight and Passenger - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 514: Statewide and Megaregional Travel Forecasting Models: Freight and Passenger documents current practices and emerging trends with travel forecasting models. The report explores the motivation for and capabilities of statewide and megaregion models, options for extending them and challenges states face doing so, data requirements, how they are used and integrated with other models, institutional constraints, and emerging trends and methods. Several related issues were investigated as well, including performance monitoring, alternative forecasting approaches, and how states are addressing hot topics such as pricing and congestion, multi-state corridors, and new transportation modes.
Keywords: Transportation and Infrastructure

Improving the Resilience of Transit Systems Threatened by Natural Disasters, Volume 2: Research Overview - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Transit Cooperative Research Program (TCRP) Web Only Document 70: Improving the Resilience of Transit Systems Threatened by Natural Disasters, Volume 2: Research Overview summarizes elements of the research effort that offers practices for transit systems of all sizes to absorb the impacts of disaster, recover quickly, and return rapidly to providing the services that customers rely on to meet their travel needs. It also explores additional research needs that have been identified during the course of the study. The report is accompanied by Volume 1: A Guide, Volume 3: Literature Review and Case Studies, and a database called resilienttransit.org to help practitioners search for and identify tools to help plan for natural disasters.This website is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.TRB hosted a webinar that discusses the research on March 12, 2018. A recording is available.
Keywords: Transportation and Infrastructure

Public Transportation Guidebook for Small- and Medium-Sized Public-Private Partnerships (P3s) - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Transit Cooperative Research Program (TCRP) Research Report 191: Public Transportation Guidebook for Small- and Medium-Sized Public-Private Partnerships (P3s) serves as a resource to explore, evaluate, initiate, plan, and implement small- and medium-sized public-private partnership (P3) initiatives. The guidebook addresses why and when to consider P3s for small- and medium-sized initiatives, what types of initiatives may be undertaken, and how to effectively undertake these initiatives.A P3 Project Screening Checklist, a Microsoft Excel spreadsheet, accompanies the guidebook and may assist transit agencies with screening and evaluating a P3 initiative.Disclaimer - This spreadsheet is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Practices for Evaluating the Economic Impacts and Benefits of Transit - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Transit Cooperative Research Program (TCRP) Synthesis 128: Practices for Evaluating the Economic Impacts and Benefits of Transit provides state-of-the-practice information for transit agencies to help them in incorporating economic benefits and impacts into their decision-making processes, which may lead to more sustainable funding solutions for transit agencies. The report describes the methods used for assessing transit economic impacts and benefits, the types of effects that are covered by these methods, and the ways that agencies are using the information obtained for planning, prioritizing, funding, and stakeholder support.
Keywords: Transportation and Infrastructure

Decision-Making Toolbox to Plan and Manage Park-and-Ride Facilities for Public Transportation: Research Report and Transit Agency Case Studies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Transit Cooperative Research Program (TCRP) Web-Only Document 69: Decision-Making Toolbox to Plan and Manage Park-and-Ride Facilities for Public Transportation: Research Report and Transit Agency Case Studies supplements TCRP Research Report 192: Decision-Making Toolbox to Plan and Manage Park-and-Ride Facilities for Public Transportation: Guidebook on Planning and Managing Park-and-Ride. TCRP Web-Only Document 69 presents information gathered in the development of the guidebook, summarizes the technical research, and presents the in-depth park-and-ride case studies.
Keywords: Transportation and Infrastructure

Improving the Resilience of Transit Systems Threatened by Natural Disasters, Volume 3: Literature Review and Case Studies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Transit Cooperative Research Program (TCRP) Web Only Document 70: Improving the Resilience of Transit Systems Threatened by Natural Disasters, Volume 3: Literature Review and Case Studies includes appendicies that outline the literature reviewed and 17 case studies that explore how transit agencies absorb the impacts of disaster, recover quickly, and return rapidly to providing the services that customers rely on to meet their travel needs. The report is accompanied by Volume 1: A Guide, Volume 2: Research Overview, and a database called resilienttransit.org to help practitioners search for and identify tools to help plan for natural disasters.This website is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.TRB hosted a webinar that discusses the research on March 12, 2018. A recording is available.
Keywords: Transportation and Infrastructure